Pengaruh Proprioceptive Exercise Terhadap Pengurangan Nyeri Pada Kondisi Osteoarhtritis Knee - Aprilia, Dian; , Maskun Pudjianto, S.Pd, M.Kes, d; , Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: By increasing it old age, physiological unction experience of the degradation of process degenerative effect (older) so that disease was not catching many emerging at old age the example of osteoarthritis knee. Osteoarthritis knee was marked with, growth osteofit at side of joint, stretch the joint capsule, infection incidence, and weak it connective muscle of joint causing pain in bone. Hence needing the existence of proprioceptive exercise practice, this method was effective to lessen the pain in bone and improve the joint stability. Research Purpose: to identify advanteges of proprioceptive exercise practice for increasing pain in bone at osteoarthritis knee condition. Research Benefit: proprioceptive exercise practice could be increasing pain in bone at osteoarthritis knee condition Research Method: Research type used by quasi experiment research by Pretest-Posttest Control Group Design. Sum up the sampel at this research equal to 14 samples, way of intake was using purposive sampling method that was sample taken at random pursuant to with the criterion of inclusi and exclusi. Statistical analysis was using Wilcoxon test to the influence test, and Mann Whitney test for the test of influence different. Measuring instrument of pain in bone was using numeric rate scale (NRS). Research Result: The statistical analysis was obtained result of proprioceptive exercise where result test the influence at pain in bone group treatment at the moment awaken from position sit have p value = 0,016 and pain in bone at the moment step on straircase 3 trap have p value = 0,015. Result of test show that the existence of change which significant with the value (p<0,05). While at different influence test there were change which significant at pain in bone at the moment walk 15 metre have p value = 0,006 because (p<0,05). Conclusion: Statistically significant proprioceptive exercise with the practice during 3 times one week during 4 week (1 month) could be lessen the pain in bone at osteoarthritis knee condition at the time of pain in bone awaken from position sit and moment of pain in bone step on straircase 3 trap